Hereditary angioedema diagnosis evaluation score (HADES): A new clinical scoring system for predicting hereditary angioedema with C1 inhibitor deficiency - Ricardo Zwiener, MD; Rafael Zamora, MD; Carlos María Galmarini, MD, PhD; Laura Brion, PhD; Laura Arias, MD; Andrea Pino, MD; Paula Rozenfeld, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Diagnosis of hereditary angioedema (HAE) poses challenges because of its rarity and its overlapping symptoms with allergic and gastrointestinal conditions, resulting in misdiagnosis. Objective: We developed a predictive score using clinical variables for suspected HAE patients with C1 inhibitor deficiency (HAE-C1INH) to increase suspicion of HAE and thus improve diagnosis. Methods: The HADES (HAE diagnosis evaluation score) study used a nationwide retrospective cohort of individuals with suspected HAE-C1INH in Argentina. A questionnaire was designed to collect relevant clinical information on possible predictors for HAE. Blood samples were analyzed for C1-INH/C1q levels and C1-INH function. A predictive score was developed from the odds ratios derived from multivariate logistic regression analysis. Results: The study included 2423 individuals (1642 suspected index cases and 781 family cases). Only patients with confirmed HAE types I or II (n = 499) were included in the final analysis; acquired angioedema/F12 gene variants were excluded. Eight clinical variables were identified as independent predictors of HAE: age at onset ≤20 years, recurrent limb edema, abdominal pain, vomiting, trauma as a trigger, absence of wheals, family history of angioedema, and recurrent edema lasting ≥24 hours. The predictive score demonstrated favorable performance in identifying HAE cases within the index population (range, 0-18.5), with low scores (1.5-6.5) associated with high sensitivity (100%) and negative predictive value (100%), and high scores (≥15) associated with high specificity (99.4%) and positive predictive value (75.0%). Conclusions: The predictive HADES offers a simple and efficient method for improving testing for suspicion of HAE by using clinical parameters. Further validation studies are required to confirm its reliability and accuracy.